Talkshow Inspiratif untuk Memahami Makna Syukur dalam Meningkatkan Kesehatan Mental Santri - Rosita, Tita; Ayu Leofianti, Annisa Rizki; Apriliana, Novita F.; Mahdiyah, Fitri A. (Ma'soem University, 2025)
The purpose of the inspirational talk show is to understand the meaning of gratitude in improving the mental health of students. The talk show activity was held at the Ash-Shalihin Qur'an House, South Jakarta and the participants who attended were students with an age range of 7-12 years. The method used in community service is using the Service Learning (SL) method. The talk show activities in this service go through three stages, namely (1) identifying the mental health conditions of students in memorizing the Qur'an; (2) the stage of providing material about the meaning of gratitude; (3) discussion and question and answer sessions with students. Based on the results of the talk show, the first session of identification obtained data that some students are still less consistent in murojaah or repeating the memorization of the Qur'an that they have learned, so they easily forget; when studying, they are often distracted by playing; sometimes some still feel forced to memorize so that the learning mood is not good, so they end up chatting more with their friends. As for after being given material and discussion sessions, the result is that on average, the santri have an increased understanding of the meaning of gratitude which can make them have a mentally healthy person.